The latecomer - Korelitz, Jean Hanff, 1961- (Celadon Books, 2022)
"From the New York Times bestselling author of The Plot (a Tonight Show Summer Read pick) and You Should Have Known, adapted as HBO's The Undoing, Jean Hanff Korelitz's The Latecomer is the story of three siblings, desperate to escape one another, and the upending of their family by the late arrival of a fourth. The Oppenheimer triplets have been reared with every advantage: wealth, education, and the determined attention of at least one of their parents. But neither Harrison (the smart one), Lewyn (the weird one) nor Sally (the girl) suspects the devastating event that first set their family in motion, or understands how fully it has already formed them. Now, on the verge of their departure for college and desperate to escape one another at last, the triplets are forced to contend with an unexpected complication: a fourth Oppenheimer sibling, formerly a leftover embryo from their own long ago in vitro genesis, has just been born. What has possessed their parents to make such an unfathomable decision? How can the triplets begin to imagine the impact this unwanted latecomer will have on their lives, and the ways she will work to bring them home? The Latecomer is a tender and witty family story from an accomplished author, known for the depth of her character studies and her love of a plot twist"--